Aspects of the economy of Mari in the Middle Bronze Age : foreign trade in the old Babylonian period (c. 1830-1758 B.C.E.) - Cornelius, I. (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1985.